TINJAUAN YURIDIS TERHADAP PEMBELIAN BARANG ELEKTRONIK REKONDISI - Amarulazhar, Amar; Yuniar Rahmatiar; Muhamad Abas (LPPM STIH Awang Long, 2023)
This study aims to determine the position of the parties in purchasing electronic reconditioned goods and the mechanisms for purchasing reconditioned electronic goods as well as legal protection for consumers in purchasing electronic reconditioned goods. The research method used in this study is a normative juridical approach, namely a legal approach that is carried out by examining the rules or rules that relate to the purchase of reconditioned electronic goods, from the perspective of consumer protection law, by studying literature or by reading, quoting and studying theory. related to the problem being studied. Then the main data used is secondary data and supporting data is primary data. The data analysis technique in this study uses the interpretation method, which contains opinions or theoretical views on something, in this case of course the theoretical views refer to applicable laws and regulations, books, journals, decisions and other sources that can be accounted for. By looking at the results and discussion, it can be concluded that the position of the parties in purchasing electronic reconditioned goods is unbalanced, in which case the consumer is in a weak position. The mechanism for buying electronic refurbished goods is the same as buying and selling in general.